Effect of darbepoetin alfa on exercise tolerance in anemic patients with symptomatic chronic heart failure : A randomized, double-blind, placebo-controlled trial - PONIKOWSKI, Piotr; ANKER, Stefan D; ROSEN, Stuart D; POOLE-WILSON, Philip A; BANASIAK, Waldemar; COATS, Andrew J. S; MCDONALD, Ken; SZACHNIEWICZ, Joanna; OKONKO, Darlington; LEDWIDGE, Mark; ZYMLINSKI, Robert; RYAN, Enda; et al. (Journal of the American College of Cardiology, 2007)
This study sought to investigate whether darbepoetin alfa, an erythropoiesis-stimulating protein (ESP), improves exercise capacity in patients with symptomatic chronic heart failure (CHF) and anemia. Anemia is common in patients with CHF. In a multicenter, randomized, double-blind, placebo-controlled study, CHF patients with anemia (hemoglobin > or =9.0 to < or =12.0 g/dl) received subcutaneous placebo (n = 22) or darbepoetin alfa (n = 19) at a starting dose of 0.75 microg/kg every 2 weeks for 26 weeks. The primary end point was change in exercise tolerance from baseline to week 27 as measured by peak oxygen uptake (ml/min/kg body weight). Other end points included changes in absolute peak VO2 (ml/min), exercise duration, and health-related quality of life. Differences (95% confidence interval) in mean changes from baseline to week 27 between treatment groups were 1.5 g/dl (0.5 to 2.4) for hemoglobin concentration (p = 0.005), 0.5 ml/kg/min (-0.7 to 1.7) for peak VO2 (p = 0.40), 45 ml/min (-35 to 127) for absolute peak VO2 (p = 0.27), and 108 s (-11 to 228) for exercise duration (p = 0.075). Patients receiving darbepoetin alfa compared with placebo had an improvement in self-reported Patient's Global Assessment of Change (79% vs. 41%, p = 0.01) but no significant differences in the Kansas City Cardiomyopathy and Minnesota Living with Heart Failure Questionnaire scores. Darbepoetin alfa was well tolerated. In patients with symptomatic CHF and anemia, darbepoetin alfa increased and maintained hemoglobin concentrations and improved health-related quality of life. A trend toward increased exercise time but not peak VO2 was observed. (Impact of Darbepoetin Alfa on Exercise Tolerance and Left Ventricular Structure in Subjects With Symptomatic Congestive Heart Failure (CHF) and Anemia; http://clinicaltrials.gov/ct/show/NCT00117234?order = 1; NCT00117234).